Response of soil water content temporal stability to stand age of Haloxylon ammodendron plantation in Alxa Desert, China - Zhou, Dongmeng; Si, Jianhua; He, Xiaohui; Jia, Bing; Zhao, Chunyan; Wang, Chunlin; Qin, Jie; Zhu, Xinglin; Liu, Zijin (Frontiers in Plant Science, 2023)
Afforestation as an effective measure for wind and sand control has achieved remarkable results in northern China, and has also greatly changed the land use and vegetation characteristics of the region. It is important to study the spatial and temporal dynamics of soil water content (SWC) in different afforestation years and its temporal stability to understand the dynamic characteristics of SWC during afforestation. In order to reveal the spatiotemporal dynamic characteristics of SWC in desert area Haloxylon ammodendron (HA)plantations, in this study, five restorative-aged HA plantations in desert areas were selected and their SWC was measured in stratified layers for the 0–400 cm soil profile; we also analyzed the spatiotemporal dynamics and temporal stability of the SWC. The results showed that the SWC of HA plantations decreased with the increase in planting age in the measurement period, and the SWC of deep layers increased by more than that of shallow layers with planting age. Spearman’s rank correlation coefficients for SWC of 0–400 cm in both 5- and 11-year-old HA plantations reached above 0.8 and were highly significantly correlated; the temporal stability of SWC tends to increase as the depth of the soil layer deepens. In contrast, the temporal stability of SWC in deeper layers (200–400 cm) of 22-, 34- and 46-year-old stands showed a decreasing trend with depth. Based on the relative difference analysis, representative sampling points can be selected to monitor the regional average SWC, but for older HA plantations, the uncertainty factor of stand age should be considered in the regional moisture simulation. This study verified that it is feasible to simulate large-scale SWC in fewer observations for HA plantations younger than 11 years old, while large errors exist for older stands, especially for deeper soils. This will help soil moisture management in HA plantations in arid desert areas.